Solar System Learning Media Based On Android Mobile For Elementary School Students - Prasetyo, Budi, Endah Sudarmilah, S.T., M.Eng, Aris Budiman, S.T., M.T (2013)
Learning is an interaction process between students and teachers and source of study in teaching learning process. The lecture method has disadvantage that the interaction to be centered on teachers so teachers cannot know with certainty how far students understand about the material. The material of the solar system is actually complex, to clarify the understanding of the solar system material, need information technology support that can be applied to this material. The researcher makes design and application as interactive learning media in studying solar system material based on android mobile for elementary school students. The researcher used research and development method. Research and development method is a kind of research method that used to produce special product, and examine the effectiveness of the product. The system designing and developing with the process of producing DFD, flowchart and implemented using Android Developer Tools Bundle v21.0.1- 543035 programing tools. The result in the questionnaire assessment that has been tested in SD N 1 Singopuran, Kartasura, Sukoharjo, Jawa Tengah can be concluded that more than 80% students and teachers give respond strongly agree that this application can be as interesting and interactive learning media which help the students in studying solar system material.